Structural and Kinetic Insights Into the Molecular Basis of Salt Tolerance of the Short-Chain Glucose-6-Phosphate Dehydrogenase From Haloferax volcanii - Fuentes-Ugarte, Nicolás; Herrera, Sixto M.; Maturana, Pablo; Castro-Fernandez, Victor; Guixé, Victoria (Frontiers in Microbiology, 2021)
Halophilic enzymes need high salt concentrations for activity and stability and are considered a promising source for biotechnological applications. The model study for haloadaptation has been proteins from the Halobacteria class of Archaea, where common structural characteristics have been found. However, the effect of salt on the enzyme function and conformational dynamics have been much less explored. Here, we report the structural and kinetic characteristics of the Glucose-6-phosphate Dehydrogenase from Haloferax volcanii (HvG6PDH) belonging to the short-chain dehydrogenases/reductases (SDR) superfamily. The enzyme was expressed in E. coli and successfully solubilized and refolded from inclusion bodies. The enzyme is active in the presence of several salts though the maximum activity is achieved in the presence of KCl, mainly by an increment in the kcat value, that correlates with a diminution of its flexibility according to molecular dynamics simulations. The high KM for glucose-6-phosphate and its promiscuous activity for glucose restricts the use of the HvG6PDH as an auxiliary enzyme for the determination of halophilic glucokinase activity. Phylogenetic analysis indicates that SDR-G6PDH enzymes are exclusively present in Halobacteria, being the HvG6PDH the only enzyme characterized. Homology modelling and molecular dynamics simulations of HvG6PDH identified a conserved NLTX2H motif involved in glucose-6-Phosphate interaction at high salt concentrations, whose residues could be crucial for substrate specificity. Also, structural differences in its conformational dynamics, potentially related to the haloadaptation strategy, were determined.